The Effect of Crude Oil Price Volatility on Volatility in Tehran Stock Market GARCH Multivariate Approach - Mohammad Hassan Fotros; Maryam Hoshidari (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2016)
Oil is one of the strategic commodities in any country because it is an important input of production process. According to negative impact of oil price fluctuations on the various sectors of the Iranian economy, stock market performance is an obstacle for investors based on results and performance respectively. So, we need a detailed understanding of oil price changes on the stock index. Determination of oil prices depends on many factors, most of which are beyond the control of the producer of oil. This issue depends on oil revenues affected by fluctuations of oil prices .This paper examines the volatility of oil prices on the Stock Exchange Volatility index using a multivariate GARCH model and employs monthly data for the period May 2001 to March 2016. The stationary test as well as test ARCH, to infer the existence of Arch on the variables, using the approach BEKK volatility in crude oil prices and efficiency regarding the Tehran Stock Exchange Index has been investigated. results of this study show the significant negative relationship between volatility in crude oil prices and volatility in Tehran Stock Exchange Index and There is also a significant negative relationship between exchange rate fluctuations and show that volatility returns Tehran Stock Exchange index exists.